Lesbian in Adolescents and Prevention by Counselors - Fira Ramli (Journal of Counseling and Educational Technology, 2019)
Lesbians, gays, bisexuals and transgender people or abbreviated as LGBT have targets starting in their teens. Teenagers are expected to have found sexual orientation and sex roles according to their sex. The emergence of comfort with peers reinforces the urge to be a lesbian. The importance of prevention to avoid the risk of deviant sexual behavior. This type of research is quantitative descriptive with self-identification instrument. The total sample of 183 boarding schoolgirls obtained through purposive sampling. The results of processing instruments found 39.9% or as many as 73 students in the category were experiencing a tendency to behave lesbians. It can be interpreted that adolescents are still in a position to find identity and confusion to determine their identity so that they can still be influenced by lesbian behavior. As for prevention that can be done by the counselor is to provide information services with materials that fit the needs of adolescents, namely adolescent girls' adolescence, recognize the growth and development of adolescents, differentiate sex and gender between men and women, limit adolescent relationships over the dangers of lesbi behavior. The service material is expected to prevent the occurrence of deviant sexual behavior, namely lesbi.